Characterizing Contact Lens–Related Corneal Infiltrates: A Pilot Study. Issue 12 (December 2016) - Jansen, Meredith E.; Situ, Ping; Begley, Carolyn G.; Boree, Danielle; Chalmers, Robin L.; Osborn Lorenz, Kathrine; Wilson, Tawnya
Abstract : Purpose: To document the time course and resolution of contact lens–related corneal infiltrative events (CIEs) comparing slit-lamp images with anterior segment ocular coherence tomography (AS-OCT) images. Methods: Six silicone hydrogel (SiHy) soft contact lens (SCL) wearers presenting with newly diagnosed symptomatic CIEs were monitored with slit-lamp images, detailed drawings, and AS-OCT until the resolution of the CIE. A final follow-up visit was completed 4 weeks after CIE resolution to determine whether scar formation was present. Positive controls were 2 SiHy SCL wearers with established (inactive) corneal scars, and negative controls were 2 SiHy SCL wearers with clear corneas. High- and low-contrast logMAR visual acuities were measured, and subjective symptom questionnaires were completed at all visits. Results: Clinical signs, vision, and symptoms improved in tandem with the resolution of the CIEs as measured by imaging methods. Calibrated measures of infiltrate width from a slit-lamp biomicroscope appear to be similar to calibrated images from AS-OCT. Conclusions: Although further studies are needed to develop standardized procedures, AS-OCT can be a useful tool to characterize the development, progression, and resolution of corneal infiltrates as an objective measure of resolution and scar formation.